A Modelling Approach for Assessing the Hydrogeological Equilibrium of the Karst, Coastal Aquifer of the Salento Peninsula (Southeastern Italy): Evaluating the Effects of a MAR Facility for Wastewater Reuse. (14th May 2019) - De Filippis, Giovanna; Margiotta, Stefano; Branca, Claudia; Negri, Sergio Luigi
Abstract : The Salento Peninsula is characterized by poor surface water resources, due to the karstic nature of its territory. On the other hand, important groundwater resources are located in the deep, karst, coastal aquifer, which is of strategic importance for the economic and social development of the area. The increasing water demand, however, if not properly managed may pose serious problems to the hydrogeological equilibrium of this aquifer, which is highly susceptible to natural and anthropogenic changes and to saltwater intrusion. Taking steps from the previous works, the present paper focuses on the characterization of the deep aquifer of the Adriatic portion of the Salento Peninsula from a quantitative point of view by means of modelling tools for the simulation of groundwater dynamics. Conclusions about the extent of the saltwater intrusion phenomenon are consequently inferred. As a result of the implementation of a density-dependent flow model, the lateral extent of such phenomenon and the vertical depth of the transition zone between freshwater and saltwater were inferred, highlighting also the role of major faults which characterize the hydraulic behaviour of the karst system under exam. The model was also applied to design a Managed Aquifer Recharge facility for management and protection of the hydrogeological equilibrium of the deep aquifer. Its positive effects on the advancement of the saline front were highlighted. Model results also allowed identifying areas where the lack of data prevents a proper comprehension of the hydrogeological processes investigated, thus representing a supporting tool for planning further monitoring campaigns.